Decreased suppression of antibody-dependent cellular cytotoxicity by seminal plasma in unexplained infertility - Sakin-Kaindl, Filiz; Wagenknecht, Dawn R; Strowitzki, Thomas; McIntyre, John A; Thaler, Christian J (Fertility and sterility, 2001)
To determine whether seminal plasma (SP) from unexplained infertile males has different suppressive activity on antibody-dependent cellular cytotoxicity (ADCC) than SP from fertile males or SP from males of couples with known infertility factor.